-3(u+4)-2u=(u+1)

Simple and best practice solution for -3(u+4)-2u=(u+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(u+4)-2u=(u+1) equation:



-3(u+4)-2u=(u+1)
We move all terms to the left:
-3(u+4)-2u-((u+1))=0
We add all the numbers together, and all the variables
-2u-3(u+4)-((u+1))=0
We multiply parentheses
-2u-3u-((u+1))-12=0
We calculate terms in parentheses: -((u+1)), so:
(u+1)
We get rid of parentheses
u+1
Back to the equation:
-(u+1)
We add all the numbers together, and all the variables
-5u-(u+1)-12=0
We get rid of parentheses
-5u-u-1-12=0
We add all the numbers together, and all the variables
-6u-13=0
We move all terms containing u to the left, all other terms to the right
-6u=13
u=13/-6
u=-2+1/6

See similar equations:

| 2x+22=-11 | | 4(2a-7)=7a-33 | | 1=2(u-4)-5u | | 72=8*n | | -5m=4.0 | | 75+14x=10+19x | | c=-79+0.02/0.5 | | 12y5=5 | | 3b/4=5b-68 | | C=39.52+0.50x | | 3y-88=5y/9 | | -4(y+1)+6y=2(y+27)-8 | | 6x-24x/7=4-2 | | -27+2n=-3+8(2n+4) | | 60=-0.3x−30 | | 33a+27=12a+174 | | 377.00=190+0.85x | | 5s-4=40 | | q/18+(-348)=-318 | | 2x/3=3x-63 | | 2q/3=6q-96 | | 5p/6=4p-76 | | -4(4+n)=20+8n | | 177=15y-33 | | -26c-52=c+893 | | 4b+1/5+7=9b-124 | | 12y+13=9y+28 | | 177=n/8+156 | | 3c/4=5c-136 | | 3y/4=5y-153 | | M=4b=3 | | u+308=-6u-28 |

Equations solver categories